Respuesta :
Answer:
see below
Step-by-step explanation:
y = 8x − 9
y = 4x − 1
Since both equations are equal to y, we can set them equal to each other
8x-9 = 4x-1
Subtract 4x from each side
8x-4x-9 = 4x-4x-1
4x-9 = -1
Add 9 to each side
4x-9+9 = -1+9
4x = 8
Divide each side by 4
4x/4 = 8/4
x=2
Now find y
y = 4x-1
y = 4(2)-1
y = 8-1
y = 7
(2,7)
The point of intersection when the 2 lines are graphed is (2,7)
![Ver imagen wegnerkolmp2741o](https://us-static.z-dn.net/files/d55/6c9553eeaea0f5d8aaf8ef9963f5d967.jpg)
Answer:
Part A
y = 8x − 9 (1)
y = 4x − 1 (2)
If using elimination,
Multiply (2) by -2 and add to (1)
Solve for y
Then using any equation, solve for x
y = 8x - 9
-2y = -8x + 2
Part B
-y = -7
y = 7
7 = 8x - 9
16 = 8x
x = 2
The point of intersection of two lines is also the solution to the system of equations of those lines
Hence, these two lines intersect at (2,7)